Beyond binding change: the molecular mechanism of ATP hydrolysis by F1-ATPase and its biochemical consequences - Nath, Sunil (Frontiers in Chemistry, 2023)
F1-ATPase is a universal multisubunit enzyme and the smallest-known motor that, fuelled by the process of ATP hydrolysis, rotates in 120o steps. A central question is how the elementary chemical steps that take place in the three catalytic sites are coupled to mechanical rotation. Here we carry out cold chase promotion experiments and measure the rates and extents of hydrolysis of preloaded bound ATP and promoter ATP bound in the catalytic sites. We find that rotation is caused by the electrostatic free energy change associated with the ATP splitting reaction followed by Pi release. The combination of these two processes occur sequentially in two different catalytic sites on the enzyme, thereby driving the two rotational sub-steps of the 120o rotation. The mechanistic implications of this finding are discussed based on an overall energy balance of the system. General principles of free energy transduction are formulated and their important physical and biochemical consequences are analyzed. In particular, how exactly ATP performs useful external work in biomolecular systems is pinpointed. A molecular mechanism of steady-state, tri-site ATP hydrolysis by F1-ATPase that is consistent with the physical laws and principles and the body of available biochemical information is developed. Taken together with previous results, the coupling scheme is now essentially complete. A mathematical model for estimation of economics and opportunity cost in choosing between competing theories is constructed based on seminal works in human capital theory.